Prediction of Facial Profile Based on Morphometric Measurements and Profile Characteristics of Permanent Maxillary Central Incisor Teeth - N Raghavendra; Venkatesh V Kamath; Krishnanand P Satelur; Komali Rajkumar (Wolters Kluwer Medknow Publications, 2015)
The computation of facial profile from dental morphometrics has been a subject of great interest in forensic odontology. The use of teeth to draw a profile and facial features is valuable in times of mass disasters when body remains are unavailable due to extreme destruction. This study aims to identify and evaluate applicable parameters in the permanent maxillary central incisors and the face of an individual. A correlation of these parameters establishes a mathematical equation that further charts a tooth-facial profile table. Thirty soft and hard tissue landmarks on the face in the frontal and the lateral profiles (using standardized photographs) and seven landmarks on the facial/labial surface of the clinical crown of the permanent maxillary central incisor (using casts of the maxilla) were identified for the study. Based on these, a set of eight horizontal and seven vertical parameters on the face and four parameters on the tooth were created for the assessment. Internal and external correlations between the two were carried out and statistically analyzed. A logistic regression was made to predict the probability of the parameters most likely to be reproduced in the creation of the facial profile, based on tooth morphometrics. The results indicated a definite correlation between the facial and the tooth parameters. Among the multiple parameters, a definite correlation in the horizontal dimension could be established between the mouth width and the mesiodistal width (MDW) of the tooth. In the vertical dimension, a definite relationship existed between the crown height of the tooth and the width of the midface (zygoma-mandible). There exist divergences in the correlation of tooth and facial parameters.